Propuesta de Intervención Social para el Fortalecimiento Organizacional de la Asociación de Productores Agroecológicos Ecovida de la Comunidad San Agustín de la Ciudad de Loja - Cueva Jara, Santos Alcibar (2016)
This work is part of a descriptive inquiry and literature review with a qualitative approach on the incidence style dirigencial leadership in organizational development and the need for intervention by the Social Worker, perceived by managers and partners Ecovida Association the St. Augustine community of the city of Loja. The design is established on the basis of comparison of the results they yielded interviews with community residents, partners and directors of the association said, also raises the fundamental need to generate a process of analysis, aimed to propose dynamic human organizational, from a quality approach. The results allow assert that the form of leadership exercised by the managers in the Ecovida association is democratic, showing little knowledge of the capabilities to engage its members, which does not allow organizational strengthening, nor get involved in the problems of the environment in accordance with reality; this weakness does not allow are motivated or participate in ongoing meetings, despite the existence of good relations between staff, so it is very necessary awareness campaign that promotes such attitudes and allow the generation of strategic alliances to raise the level of development of the association, so the cooperation of the Social Worker is required. In this context, this paper carries a "PROPOSAL FOR SOCIAL INTERVENTION FOR ORGANIZATIONAL STRENGTHENING OF THE ASSOCIATION OF PRODUCERS agroecological ECOVIDA COMMUNITY SAN AGUSTIN CITY OF LOJA" which is intended as a contribution to both managers and partners can broaden their views about their actions and functions in the partnership, reflecting whether they influence organizational development valuing the contribution they could offer. To achieve this proposal a methodology based on various methods like the scientist, who was present throughout the entire investigation merging clearly and precisely the theory and practice was used; the analytical method allowed interpreting field information obtained, while the literature method reinforced the process from the scientific perspective; in inductive deductive I defined the problem, analysis and conclusions and finally with the synthetic method to establish appropriate recommendations. It should be noted that the 5 survey technique was an effective means of gathering information, which aided by the interview allowed a clear view of the problem investigated. Another technique used is the SWOT, which showed in detail the strengths and weaknesses to improve the current situation. It is noted that this work may be significant for other fraternal organizations or similar purposes, wishing to implement different and innovative strategies that are effective in strengthening the dirigencial leadership, and efficiency to be gained with the contribution of the Social Worker in organizational development.